Fabrication Of Silica Water Filter From Rice Husk Waste Product Via Slip Casting Method - Sufi Abdul Shukor, Muhammad Syahmie; Ahmad, Sufizar; Muslem, Muhammad Firdaus; Mat Noor, Fazimah; Abd. Rahman, Hamimah; Mahzan, Shahruddin; Jaidi, Zolhafizi (2024)
This research focuses on utilizing amorphous silica for silica water filters from rice husk waste products that can be obtained from the area of Pasir Puteh, Kelantan. This research aims to fabricate silica water filters by using the slip casting method and investigate their physical properties. Amorphous silica with very low residual carbon content (approximately 1.0 wt.% residual carbon) was successfully produced by burning silica rice husk in a furnace at 500 °C. The compositions of silica used to fabricate water filter are 50 wt.%, 60 wt.% and 70 wt.%. The bentonite was used as the binder. The fabricated silica water filters were then sintered at 1100 °C. Various characterization such as X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray (EDX) and water absorption analysis were carried out. The findings suggest that the slip casting technique is viable for manufacturing silica water filters, as evidenced by the energy dispersive X-ray (EDX) analysis. This analysis reveals the presence of silicon (Si) and oxygen (O) in all the composition. In conclusion, by utilizing amorphous silica gathered from burning rice husk waste not only promotes sustainability but also results in filters with notable physical properties. 50 wt.% silica is the best composition for fabricating the silica water filter based on the highest rate of water absorption analysis. This approach offers a promising avenue for producing eco-friendly and efficient water filtration systems.